PA.05 The spiritual impact of stillbirth on bereaved parents: a qualitative study. (9th June 2014) - Nuzum, D; Meaney, S; O'Donoghue, K
Abstract : Objective: Stillbirth is recognised as one of the most difficult bereavements for parents with life-lasting impact. This study explores the spiritual impact of stillbirth on parents who were cared for in an Irish tertiary maternity hospital (8, 500 births per annum) where the stillbirth rate is 4.6/1000. Study design: Semi-structured qualitative interviews lasting 31–104 min were conducted with 12 mothers and 5 fathers bereaved following stillbirth. The participants were purposively sampled from each of the years 2008, 2010 and 2013. The data were analysed using Interpretative Phenomenological Analysis. Results: Stillbirth had a profound and enduring impact on each of the parents interviewed. The data revealed five main themes: Searching for Meaning, Maintaining Hope, Relationships, Importance of Personhood and Protective Care. Most parents felt their spiritual needs were not addressed adequately while in hospital. Those who were prepared for the possible death of their baby found it easier to find meaning in their loss. Most parents revealed that they struggled spiritually. All parents continue to experience close connection and enduring bonds with their baby. Conclusion: The impact of perinatal death and bereavement is considerable. This study, the first of its kind in Ireland, reveals the lived experience of spiritual wrestling and impact following stillbirth. How parents are cared for as they prepare for the death of their baby is remembered in close detail: often revisited by parents as they seek to understand their loss. These findings highlight the need for consistent and sensitive care from all who care for parents following stillbirth.